Draft Annual Plan 1976-77 Volume II Government of Jammu and Kashmir - Planning Commission (Planning Commission, 1975)
Agriculture plays a dominant role in the economy of Jammu & Kashmir State as in the rest of 2/3 rd India. Over/ of the population is engaged in the pursuit of Agriculture as a vocation. Increasing food production continues to be the main objective of developmental Programmes in the field of Agriculture. The strategy to be adopted for increasing production of food grains has to be Central around the following Increase in the area under High Yielding varieties of cereal crops both under irrigated as well as assured rainfall areas
Government of Jammu and Kashmir
Department of Planning and Development Jammu
Keywords: Multiplication and Distribution of Seeds; Seed Multiplication-cum-Demonstration Farms; Implementation of the Seed Production Programme at the existing farms; Improvement of existing small farms; Subsidy on Distribution of Seeds; Seed Processing; Soil Conditioner Demonstration Scheme; Achievement of Reclamation; Double Cropping Scheme; Strengthening of Soil Testing Laboratory; Plant Protection Scheme.